2005
DOI: 10.1534/genetics.105.040733
|View full text |Cite
|
Sign up to set email alerts
|

Gene Arrays atPneumocystis cariniiTelomeres

Abstract: In the fungus Pneumocystis carinii, at least three gene families (PRT1, MSR, and MSG) have the potential to generate high-frequency antigenic variation, which is likely to be a strategy by which this parasitic fungus is able to prolong its survival in the rat lung. Members of these gene families are clustered at chromosome termini, a location that fosters recombination, which has been implicated in selective expression of MSG genes. To gain insight into the architecture, evolution, and regulation of these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 102 publications
3
90
0
1
Order By: Relevance
“…Telomeres made up of simple sequence repeats vary in sequence among organisms, although the strand that reads 59 to 39 toward the chromosome end tends to be G-rich. For example, the telomeres of the ascomycete fungus Saccharomyces cerevisiae consist of a TG-rich repeat sequence (Walmsley et al 1984), plant chromosomes typically end in (TTTAGGG) n (Richards and Ausubel 1988), and chromosomes of mammals (Meyne et al 1989) and many filamentous fungi (Schechtman 1990;Coleman et al 1993;Farman and Leong 1995;Bhattacharyya and Blackburn 1997;Keely et al 2005) end in (TTAGGG) n .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Telomeres made up of simple sequence repeats vary in sequence among organisms, although the strand that reads 59 to 39 toward the chromosome end tends to be G-rich. For example, the telomeres of the ascomycete fungus Saccharomyces cerevisiae consist of a TG-rich repeat sequence (Walmsley et al 1984), plant chromosomes typically end in (TTTAGGG) n (Richards and Ausubel 1988), and chromosomes of mammals (Meyne et al 1989) and many filamentous fungi (Schechtman 1990;Coleman et al 1993;Farman and Leong 1995;Bhattacharyya and Blackburn 1997;Keely et al 2005) end in (TTAGGG) n .…”
mentioning
confidence: 99%
“…These traits also are likely to be adaptive. In microbial pathogens of humans, such as the protists Plasmodium falciparum (malaria) and Trypanosoma brucei (sleeping sickness) and the ascomycete fungus Pneumocystis carinii, the subtelomeres contain families of variant genes coding for surface proteins (Hernandez-Rivas et al 1997;Barry et al 2003;Keely et al 2005). These organisms use various mechanisms to switch expression among different gene copies-a strategy that allows them to evade the immune system (Graham and Barry 1995;Rudenko et al 1996;Sunkin and Stringer 1996;Wada and Nakamura 1996;Scherf et al 1998).…”
mentioning
confidence: 99%
“…10) (Keely & Stringer 2009). There are 17 chromosomes in P. carinii (Hong et al 1990), indicating that on average at least 2 MSG genes are at each telomere, which is often the case in cloned terminal fragments from various chromosomes (Keely et al 2005;Wada & Nakamura 1996). Similar to the situation in T. brucei, only one MSG gene is transcribed at any time.…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 99%
“…Computational analysis of MSG gene sequences suggested that these genes commonly undergo recombination (Keely & Stringer 2009;Keely et al 2005;Wada & Nakamura 1996), which is not unlike the VSG switching in T. brucei. Similar to VSG, MSG is also the last transcribed gene on the chromosome (Keely et al 2005;Wada & Nakamura 1996). The proximity of MSG genes to telomeres suggests that the MSG switching events might also be regulated by the telomere structure, although this has not be investigated at all.…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 99%
“…In Candida glabrata (De Las Penas et al, 2003) nearly 24 adhesin encoding genes were located at telomere regions, and, in P. carinii clusters of major surface antigen genes have been bioinformatically predicted at every chromosome end (Keely et al, 2005). A similar situation was reported in P. falciparum and Trypanosoma brucei where families of antigen surface proteins inducing immune responses are encoded in telomere regions as part of a pathogen's mechanism to amplify and diversify surface antigen genes to avoid host recognition, as it has been hypothesized (Barry et al, 2003).…”
Section: Fungal Telomeres -A Bioinformatics Approachmentioning
confidence: 99%